Contesting Western Dominant Narratives of Terrorism in Lionel Shriver’s We Need to Talk About Kevin and Kamila Shamsie’s Home Fire - Nada Syifa Fitriani; Hasnul Insani Djohar; Nada Tayem (Muslim English Literature, 2026)
This research examines how Shiver’s We Need to Talk About Kevin (2003) and Shamsie’s  Home Fire expose Western double standards in representations of terrorism and reveal how anti-Muslim bias constructs Muslims as inherently associated with terrorism. The motivation for the study is the continued link of Muslims with terrorism as opposed to sharply contrasting portrayals of non-Muslim perpetrators of comparable atrocities. It explores how these novels deconstruct the supposed neutrality of the War on Terror rhetoric by revealing the ideological assumptions and double standards that inform portrayals of terrorism. The current study applies Edward Said’s theory of Orientalism to scrutinize the Western biases in the depiction of terrorism in both novels. It also uses Critical Terrorism Studies to examine how the concept of terrorism is formed through hegemonic Western discourses. This study used a qualitative approach to conduct a close textual analysis of the tales of Parvaiz and Kevin, exploring how their differing representations reveal underlying ideological prejudices. The findings suggest that Western representations of terrorism disproportionately link Muslim identities to terrorism and that white perpetrators are more likely to be explained in terms of individual or psychological factors rather than being labeled as terrorists, even when their actions meet widely accepted definitions of terrorism. These differing portrayals show that the vocabulary of the War on Terror is ideologically informed, rather than consistently applied across cases. Ultimately, the two books question the assumption that this discourse is neutral or objective by showing the racialized and unequal frameworks through which terrorism is represented.